A case study in forensic soil comparison. Issue 2 (27th November 2021) - Guo, Hongling; Yao, Yifeng; Li, Yameng; Wang, Ping; Hu, Can; Yuan, Meiqing; Mei, Hongcheng; Zhu, Jun
Abstract: Soil examination can provide useful forensic information about the spatial location and suspect's activities. Many techniques have been applied for soil comparison and provenance determination in criminal investigations. Pollen and diatom identification, which has the potential to provide an independent ecological assessment of soil evidence, is currently underused in forensic soil analysis. This work presents a case study of application of these methods to help criminal investigation in a murder case, which happened in an irrigation ditch in Hunan Province, southern China. Soils from the suspect's clothes, the exact crime scene spot in the irrigation ditch, along the ditch and the reference ditches were collected and analyzed. In addition to the element and mineral analysis, pollen and diatom assemblages were analyzed for further comparison. The statistical methods of hierarchical cluster and cosine similarity analysis were carried out to assist in soil comparison and provenance determination. The results showed that soil on the suspect's clothes had a high probability to share the same source with the soil from the crime scene in the irrigation ditch. The suspect confessed to murder based largely on the soil examination result even without other evidences.